Research progress of Mendelian randomization analysis for glaucoma etiology - Jiao-Man Wang; Yin-Wei Song; Jing-Jing Su; Li-Cheng Fu; Di Gong; Ping Guo; Wei-Hua Yang (International Journal of Ophthalmology)
In recent years, Mendelian randomization (MR) has been increasingly utilized, leveraging genetic variants as instrumental variables. This approach significantly mitigates confounder effects and reverse causation, precisely clarifying the causal links between exposures and outcomes. MR's unique advantages have made it instrumental in medicine, especially in elucidating glaucoma's etiology. It facilitates the identification of potential risk factors, laying the groundwork for developing preventative and therapeutic strategies against glaucoma. Recent MR research has delved into diverse potential glaucoma risk factors, including behavioral habits, metabolic profiles, and their causative linkage to the disease. This review encapsulates MR's analysis in glaucoma etiology, heralding new avenues for understanding underlying mechanisms and establishing causality.